Use of different designed needle-free connectors: a snapshot of central venous catheter intraluminal blood occlusion and central line–associated bloodstream infection in hospitals - Lange, Victor R. (International Journal of Infection Control, 2024)
Background: Needle-free connectors (NCs), originally designed to improve the safety of healthcare workers, are increasingly being used to mitigate central line–associated bloodstream infection (CLABSI) and central venous catheter intraluminal blood occlusion (CVC-IBO) in patients. There are numerous NCs on the market, with varied internal and external designs and features. Objectives: The purpose of this study was to compare the frequency, clinical, and financial impact of CVC-IBO and CLABSI among 16 California (USA) hospitals using differently designed NCs. Method: Data were collected by sending a survey to the hospitals, which had varying bed capacities and patient populations that were committed to reducing CVC-IBO and CLABSI. In each hospital, CLABSI rates were tracked as defined by the National Healthcare Safety Network. Results: Hospitals using the BD MaxPlus™ or MaxZero™ Needle-free Connector, the only device with a solid external access surface, were found to have a significantly lower CLABSI rate (1.32 vs. 2.95 per 1,000 central-line days [CLDs]; P = 0.0052) and CVC-IBO rate (1.51 vs. 4.04 per 1,000 CLDs; P = 0.0065) versus those using devices with a nonsolid access surface. Conclusion: Hospitals using the MaxPlus™ or MaxZero™ NC also had significantly higher cost saving (per 100 patient days) associated with lower use of tissue plasminogen activator versus devices with a nonsolid access surface ($219 vs. $510 USD; P = 0.01). These results highlight the clinical importance of NC design components and their contributions to risk of CLABSI and catheter occlusion.